The role and portrayal of the king in the Esther narrative : a narratological-synchronic reading of the Masoretic text of the Esther narrative - Le Roux, J.H. (Jurie Hendrik), 1944- (University of Pretoria, 2013)
Thesis (PhD (Old Testament))--University of Pretoria, 1999.